The Mechanism of Activation of Cat Plasma by Streptokinase* - Mootse, G; Fleming, L.B; Cliffton, E.E (Thrombosis and Haemostasis, 1965)
1. The mechanism involved in the inactivation of cat plasma, serum, and plasma euglobulin by different concentrations of SK has been demonstrated.2. Two different caseinolytic entities were graphically differentiated. They were characterized by their time of formation and stability studies.3. With suboptimal SK concentration the development of the caseinolytic activity consisted of an initial rapid phase, followed by a slowly rising activity ; beta plasmin. With optimal SK concentration only the initial rapid caseinolytic activity was obtained (alpha plasmin).4. It is suggested that beta plasmin was formed by a reversible reaction and was inactivated when substrate was not present. With increasing SK concentration alpha plasmin formation competed with the beta plasmin formation.5. A comparison of potential caseinolytic activity of cat plasma, serum, and plasma euglobulin to beta and alpha plasmin is present.